2021
DOI: 10.2147/copd.s299819
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-Day Variability of Parameters Recorded by Home Noninvasive Positive Pressure Ventilation for Detection of Severe Acute Exacerbations in COPD

Abstract: Background: Home noninvasive positive pressure ventilation (NPPV) can be considered not only as an evidence-based treatment for stable hypercapnic chronic obstructive pulmonary disease (COPD) patients, but also as a predictor for detecting severe acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Methods: In this retrospective observational study, we collected clinical exacerbations information and daily NPPV-related data in a cohort of COPD patients with home NPPV for 6 months. Daily chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Some methods, based on self-reported symptoms or manually entered data [6][7][8][9][10] are limited, since they depend on subjective assessment and on patient compliance. Others have been focusing in remote monitoring devices, enabling automatic follow-up of physiological data and reducing the need for intervention for data acquisition by patients or the health team [11][12][13][14][15][16]. Some of the methods described employ an online learning process, that can be considered as a novelty detection approach.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Some methods, based on self-reported symptoms or manually entered data [6][7][8][9][10] are limited, since they depend on subjective assessment and on patient compliance. Others have been focusing in remote monitoring devices, enabling automatic follow-up of physiological data and reducing the need for intervention for data acquisition by patients or the health team [11][12][13][14][15][16]. Some of the methods described employ an online learning process, that can be considered as a novelty detection approach.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of exacerbation prediction, one frequent hypothesis is that changes in the breathing pattern may occur before exacerbation. More specifically, some authors have found that a significant change in breathing rate may be related to an exacerbation event [11,13,14,16].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…According to epidemiological investigation, 22-40% of COPD patients have moderate or severe exacerbation at least once a year (3). AECOPD refers to the acute exacerbation of respiratory symptoms in patients with COPD that requires additional therapy (5,6). Treatment of patients with AECOPD requires the use of bronchodilators, glucocorticoids, antibiotics, and other medications.…”
Section: Introductionmentioning
confidence: 99%